Investigation of Relationship Between Google Cost-Per-Click and Search-Volume on Keyword of Chicago Tours - Komleh, Ramin Abolghasemi (Journal of Information Systems and Informatics, 2023)
Pay-per-click is one of common and important ways in online advertising through Google; but some keywords are usually expensive and this issue is visible through Google cost-per-click in Google keyword planner tool. It has done many research work in Google advertising formats, but place of studies in field of relationship between Google cost-per-click and keyword search-volume, especially in tourism area is blank. This paper tries to answer of this main question that is there a significant relationship between cost-per-click and keyword search-volume and the number of keyword's word? In other words, does cost-per-click increase or decrease, based on keyword search-volume and the number of keyword's word (multi-word keyword or hyper focused keyword phrases)? Chicago auspicates a mighty increase in tourism 2022 as its announcement an 86 percent growth in visitors in 2021 compared to 2020 and choosing the right keyword in Google search engine by travel agencies can lead to more sales. In this research, I sampled 100 search result through combination of ″chicago+tours″ as a search keyword on google.com (Google USA) and Google keyword planner daily data (December 26, 2022) based on the last 7-10 days, and via regression analysis with least squares and loess model, I tried to investigate the relationship between search-volume and cost-per-click and it will help scholars in future research in this area. This study was carried out within the scope of selected keyword in tourism area in form of cross-sectional. I find that there is no significant relationship between short-tail keywords and cost-per-click. The result of this research shows that some medium or long-tail keywords are more expensive than short-tail keywords with more search results. Another result that was observed is the lack of significant relationship between keyword search-volume and its cost-per-click, so that in some cases, high-search keywords are cheaper than keywords with a low-search.
Keywords: Google Ads . Google AdWords . Pay-per-Click PPC . Cost-per-Click CPC